Analisis Yuridis tentang Pendaftaran Tanah Menurut Peraturan Pemerintah Nomor 24 Tahun 1997 - Nayla Lutpiana Dewi; Shafira Nur Annisa; Putri J Lesikal Amanda Z; Asmak Ul Hosnah (Departement of Mathematics Education, 2024)
Landregistration according to government regulation Number 24 of 1l997 is one of the important aspects of the important regulations in and ownership and use regulations in Indonesia. This regulation incudes various rules and procedures that must be followed by land owners or interested parties in managing land. This and registration aims to crealte legal certainty and transparency in and ownership, as well as encourage investment and sustainalble development. Land registraltion alccording to government regulation Number 24 of 1997 is a very important step in managing land in Indonesia, which has significant implications for the body that confirms land ownership rights, protects the rights of the parties invoved, and encourlges sustainalble development in this country. (Dr. Urip Salntoso, S.H., 2010:1).